2013
DOI: 10.1016/j.freeradbiomed.2013.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized oxidative stress in dopaminergic cell death induced by pesticides and complex I inhibitors: Distinct roles of superoxide anion and superoxide dismutases

Abstract: The loss of dopaminergic neurons induced by the parkinsonian toxins paraquat, rotenone and 1-methyl-4-phenylpyridinium (MPP+) is associated with oxidative stress. However, controversial reports exist regarding the source/compartmentalization of reactive oxygen species (ROS) generation and its exact role in cell death. We aimed to determine in detail the role of superoxide anion (O2•−), oxidative stress and their subcellular compartmentalization in dopaminergic cell death induced by parkinsonian toxins. Oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 78 publications
2
61
0
Order By: Relevance
“…Oxidative stress was determined using dihydroethidine (DHE, 5 μM, Life Technologies/Molecular Probes), which after its oxidization to ethidium intercalates within the DNA and exhibits bright red fluorescence (Franco et al, 2007; Rodriguez-Rocha et al, 2013). Alterations in the redox state of both cytosol and mitochondrial compartments were monitored using the reduction-oxidation sensitive green fluorescent protein (roGFP) sensor as done before (Rodriguez-Rocha et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress was determined using dihydroethidine (DHE, 5 μM, Life Technologies/Molecular Probes), which after its oxidization to ethidium intercalates within the DNA and exhibits bright red fluorescence (Franco et al, 2007; Rodriguez-Rocha et al, 2013). Alterations in the redox state of both cytosol and mitochondrial compartments were monitored using the reduction-oxidation sensitive green fluorescent protein (roGFP) sensor as done before (Rodriguez-Rocha et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in the redox state of both cytosol and mitochondrial compartments were monitored using the reduction-oxidation sensitive green fluorescent protein (roGFP) sensor as done before (Rodriguez-Rocha et al, 2013). When indicated, changes in GSH content were determined by flow cytometry using monochlorobimane (mBCl, 10 μM, Life Technologies/Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
“…The role of NOX-1-dependent ROS generation during proliferation of mouse small intestinal(Jones et al, 2013) and colonic epithelium(Coant et al., 2010) has been recently proposed. Hence, it seems plausible that ROS generation pre-treatment of MODE-K cells with resveratrol before exposure to TNF-α/CHX might have activated the proliferative machinery to defend against the successive stress insult.We suggested that treatment of MODE-K cells with TNF-α/CHX might involve an early phase of mitochondria-derived ROS production inducing a later phase of NOX-derived ROS production as mitochondrial complex inhibitors show a more pronounced decrease in total ROS levels and cell death as compared to the moderate effect of the NOX inhibitor, VAS-2870(Babu et al, 2015).…”
mentioning
confidence: 99%
“…Those enzymes catalyze the removal of the toxic superoxide radical by converting it into hydrogen peroxide and molecular oxygen. 15 Research indicates that overexpression of SOD and its isoenzymes may protect efficiently against neuronal loss.…”
Section: Discussionmentioning
confidence: 99%